Planning the Balance of Health and Social Services in the United Kingdom - Boldy, Duncan; Russell, John; Royston, Geoff (Management Science, 1982)
Within the context of the U.K. background (public expenditure is being severely curtailed, at a local level health services and social services are controlled by separate organisations and there are many groups of the population for whom a number of acceptable treatments, or methods of caring, exist), the paper describes the development of a resource allocation model and its use in a local planning situation. Although based on the techniques of mathematical programming, the model does not purport to indicate a single optimum allocation of health and social services resources, but rather to calculate the resource consequences of possible alternative courses of action. As such, its use is seen as iterative, in that health and social services decision makers can review and update their assumptions in the light of the results from successive runs of model.